Central reforms in the Baltics, Russia, and the other countries of the former Soviet Union (IMF WashingtonUS, 1997)
Attempts to rank the progress that the Baltic countries, Russia and the other countries of the former Soviet Union has achieved in each of the main central banking areas surveyed and to distill an overall ranking for each country's progress thus far compared with its peer group.
DC